Las fronetras románicas en la geografía de los Balcanes: el Danubio como frontera - Francisco Javier, JUEZ GÁLVEZ (Revista de Filología Románica, 2002)
The borders of Romance and Slavonic worlds in the Balkan Peninsula’s linguistic domains lie by the west between Friulan and Venet, on the one hand, and Slovene —as well as Croatian in Istria and Dalmatia— on the other, and by the east between Rumanian and Bulgarian and, in smaller measure, Serbian (by the south), and Ukrainian (by the north). In this paper we shall focus on the border marked out by river Danube between Rumanity and Bulgarity. Due to historical and cultural reasons (common belonging to Orthodoxy, to the Ottoman Empire, to the Soviet Block...) and to strictly linguistic reasons (adscription to the central core of the socalled Balkan Linguistic Union), which are reflected in every language layer, as we shall try to illustrate at length, Rumanian and Bulgarian fill a peculiar place in their respective languages families, which is parallel to each other, despite their respective undeniable Romanity and Slavonicity. Such a relationship between these two languages we try and define as specularitas or ‘mirrorness’.